Sosialisasi dan Pelatihan Pembuatan Jamet (Jagung Cemet) Untuk Meningkatkan Perekonomian Pada Ibu-Ibu Pkk Desa Bareng Kabupaten Nganjuk - Raras Setyo Retno; Alfina Fitria Rahmasari; Anik Qoiriyah Budiyarti; Anis Dwi Hermawati; Dea Sindy Ramadhani; Dinar Noor Fadilla; Dyah Julia Wulandari; Junianto Edi Cahyono; Luluk Priani; Mohammad Aji Masaid; Oktaviani Indah Sari; Wifi Nurhaesty (AMMA : Jurnal Pengabdian Masyarakat, 2024)
The socialization activity of Jamet Making Training (Corn Cemet) for Mrs. Pkk Nganjuk Regency, especially in Bareng Village, is a part of the population with a livelihood as corn farmers. The purpose of this activity is to increase economic independence and welfare and create jobs for PKK women in Bareng Village. because MSMEs have potential strengths that can be relied on in the future development base. The sustainable impact for the PKK Women of Bareng Village is that it can be used as a strategy to improve the community's economy and increase community productivity in processing food with high selling value.